A leaky mutation in CD3D differentially affects ¿¿ and ¿¿ T cells and leads to a T¿¿¿T¿¿+B+NK+ human SCID - Gil, Juana; Busto, Elena M.; Garcillán, Beatriz; Chean, Carmen; García Rodríguez, Maria Cruz; Díaz Alderete, Andrea; Navarro, Joaquín; Reiné, Jesús; Mencía, Ángeles; Gurbindo, Dolores; Beléndez, Cristina; Gordillo, Isabel; et al. (My University, 2011)
T cells recognize antigens via their cell surface TCR and are classified as either ¿¿ or ¿¿ depending on the vari able chains in their TCR, ¿ and ¿ or ¿ and ¿, respectively. Both ¿¿ and ¿¿ TCRs also contain several invariant chains, including CD3¿, which support surface TCR expression and transduce the TCR signal. Mutations in variable chains would be expected to affect a single T cell lineage, while mutations in the invariant chains would affect all T cells. Consistent with this, all CD3¿-deficient patients described to date showed a complete block in T cell development. However, CD3¿-KO mice have an ¿¿ T cell¿specific defect. Here, we report 2 unre lated cases of SCID with a selective block in ¿¿ but not in ¿¿ T cell development, associated with a new splicing mutation in the CD3D gene. The patients¿ T cells showed reduced CD3D transcripts, CD3¿ proteins, surface TCR, and early TCR signaling. Their lymph nodes showed severe T cell depletion, recent thymus emigrants in peripheral blood were strongly decreased, and the scant ¿¿ T cells were oligoclonal. T cell¿dependent B cell functions were also impaired, despite the presence of normal B cell numbers. Strikingly, despite the specific loss of ¿¿ T cells, surface TCR expression was more reduced in ¿¿ than in ¿¿ T cells. Analysis of individuals with this CD3D mutation thus demonstrates the contrasting CD3¿ requirements for ¿¿ versus ¿¿ T cell devel opment and TCR expression in humans and highlights the diagnostic and clinical relevance of studying both TCR isotypes when a T cell defect is suspected.